Prevention of complications after surgery to remove the radicular cyst - Mansurov Abduxoshim Abdullaеvich (Science and Education, 2023)
To date, in terms of prevalence among benign tumors and other formations of the jaws, cysts are in the first place. A radicular cyst is a cavity formation filled with fluid and having a membrane. In maxillofacial surgery and surgical dentistry, cyst removal surgery is one of the most common surgical interventions.In the structure of dental diseases, patients with odontogenic cysts and cyst-like benign formations occupy a certain place, and their number does not tend to decrease. Key words: radicular cyst, cystectomy, osteoplastic material, bioplast dent, orthopantomogram.